2021
DOI: 10.1101/2021.11.26.21266917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health worker compliance with severe malaria treatment guidelines in the context of implementing pre-referral rectal artesunate: an operational study in three high burden countries

Abstract: BackgroundAppropriate clinical management of severe malaria is critical to avert morbidity and death. Recommended treatment consists of an injectable antimalarial followed by a full course of oral artemisinin-based combination therapy (ACT). Children who cannot access prompt parenteral treatment should be administered a single dose of rectal artesunate (RAS) and promptly referred to an appropriate facility for further care. This study aimed to assess compliance with the treatment recommendation in children und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The same strong effect (a 74% reduction in the risk of dying) was seen for the combination of parenteral malaria treatment followed by an ACT, as recommended by the WHO treatment guidelines [6]. Again, this is consistent with findings in the other two CARAMAL countries as reviewed by Signorell et al [45]. This importance of the oral anti-malarial treatment following injectable treatment in RHF is a very important finding from our study for three reasons: (1) its favorable effect on the health outcomes of these children, (2) because of the threat posed by artesunate monotherapy for the development of drug resistance (Awor et al pers.…”
Section: Discussionsupporting
confidence: 82%
“…The same strong effect (a 74% reduction in the risk of dying) was seen for the combination of parenteral malaria treatment followed by an ACT, as recommended by the WHO treatment guidelines [6]. Again, this is consistent with findings in the other two CARAMAL countries as reviewed by Signorell et al [45]. This importance of the oral anti-malarial treatment following injectable treatment in RHF is a very important finding from our study for three reasons: (1) its favorable effect on the health outcomes of these children, (2) because of the threat posed by artesunate monotherapy for the development of drug resistance (Awor et al pers.…”
Section: Discussionsupporting
confidence: 82%
“…As opposed to previous studies, this study considered referral to be completed only if the patient arrived at a RHF with the capacity to manage severe malaria cases. However, an analyses of the quality of care at RHFs in the CARAMAL study areas found that the treatment of children with severe malaria was often inadequate [19]. Meanwhile, some children sought post-referral treatment from a lower-level public or from a non-public provider.…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript aimed to assess referral completion of children with suspected severe malaria and its relationship with RAS implementation and administration, taking into consideration other factors influencing referral completion. The key study results are described elsewhere [18] and the treatment patterns in the RHF are described in [19].…”
Section: Introductionmentioning
confidence: 99%
“…More details about the CARAMAL project and key results are described elsewhere (Lengeler et al manuscript in preparation). 8 18 19…”
Section: Methodsmentioning
confidence: 99%